1992
DOI: 10.1107/s0021889891010890
|View full text |Cite
|
Sign up to set email alerts
|

Planar defects in β-iron disilicide (β-FeSi2) analyzed by transmission electron microscopy and modeling

Abstract: Microplanar defects were observed in fl-iron disilicide by transmission electron microscopy. They were identified as (100)[011]/2 intrinsic stacking faults by means of electron diffraction patterns and observed in highresolution lattice images. A structural model of the faults is proposed here in setting the defect position at x = ¼ within the cell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
13
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 4 publications
2
13
0
Order By: Relevance
“…Diffuse streaks along the a axis were observed with hkl conditions of k + l / = 2n, where n is an integer. Similar diffuse streaks have already been reported for the ED patterns of ␤-FeSi 2 prepared by annealing [16] and ␤-FeSi 2 thin films deposited on a Si substrate in a molecular beam epitaxy (MBE) chamber [17]. High resolution transmission electron microscopy (HR-TEM) revealed that these samples contained many planar stacking faults along the a axis.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…Diffuse streaks along the a axis were observed with hkl conditions of k + l / = 2n, where n is an integer. Similar diffuse streaks have already been reported for the ED patterns of ␤-FeSi 2 prepared by annealing [16] and ␤-FeSi 2 thin films deposited on a Si substrate in a molecular beam epitaxy (MBE) chamber [17]. High resolution transmission electron microscopy (HR-TEM) revealed that these samples contained many planar stacking faults along the a axis.…”
Section: Resultsmentioning
confidence: 57%
“…In the crystal structure of ␤-FeSi 2 , the position of the Fe1 site is identical by the displacement vector R. Thus, we split the sites of Fe2, Si1, and Si2 into Fe2a, Si1a, and Si2a (normal stacking layer) and Fe2b, Si1b, and Si2b (stacking fault layer) with the constrain of x, y + 1/2, z + 1/2. As pointed out in previous studies [16][17][18], the atomic arrangements in the (0 0 1) plane of the normal stacking layer and in the (0 1 0) plane of the stacking fault layer are close to a twin relation.…”
Section: Resultsmentioning
confidence: 69%
“…Considering now TED along the [1][2][3][4][5][6][7][8][9][10] Si axis, it must be noted that the theoretical diagram presented in figure 5b has never been observed in our samples and to our knowledge, it has never been observed in the literature. Indeed, the most commonly observed epitaxial relation is presented in figure 12 Concerning the deposition on a (001) silicon substrate the situation seems to be simpler since only the (100) /3-FeSÎ2 plane presents an acceptable mismatch.…”
mentioning
confidence: 57%
“…The atomic structure of this orthorhombic phase has been described by Dusausoy et al [1]. Data show that the natural crystal is very imperfect: numerous crystal twinnings and microplanar defects identified as intrinsic stacking faults have been reported [2,3]. (111) and (001) silicon substrates [4][5][6].…”
mentioning
confidence: 99%
See 1 more Smart Citation